Influence of stocking densities in the nursery phase on the growth of Macrobrachium amazonicum reared in net pens - de Almeida Marques, Helcio Luis; Barros, Helenice Pereira; Mallasen, Margarete; Boock, Marcello Villar; Contente Moraes Valenti, Patricia Maria [UNESP] (Elsevier B.V., 2012)
The Amazon river prawn (Macrobrachium amazonicum) is a native species with great potential for aquaculture, based on promising results obtained from experimental culture trials in Brazil. The influence of different stocking densities on the development of prawns reared in cages in the nursery phase as well as on their growth when transferred to grow-out net pens at lower densities was evaluated. In the nursery phase, juveniles I (0.157 +/- 0.014 g, 47 days old) were stocked in 0.5 m(-2) cages at densities of 400, 800 and 1200 m(-2). After 71 days, prawns were transferred to grow-out net pens of 2.0 m(-2), at a density of 20 juveniles II m(-2). The treatments were determined by the mean weights registered for the prawns (118 days old) previously stocked at 400, 800 and 1200 juveniles I m(-2) in the nursery phase: 0.94 +/- 0.07 g (T1), 0.61 +/- 0.04 g (T2) and 0.48 +/- 0.07 g (T3), respectively. In the nursery phase, mean survival was above 96%, whereas mean weights were significantly higher (P<0.05) for the density of 400 prawns m(-2). The highest biomass (276.7 g) and productivity (1152 juveniles II m(-2)) were registered at the density of 1200 prawns m(-2), differing significantly (P<0.05) from the lower densities. One month after the transfer of the animals to the net pens, there was recovery in the specific growth rate (SGR) of prawns in all treatments which was significantly higher (P<0.05) in T3 (4.01 +/- 0.36% day(-1)) and T2 (3.60 +/- 0.18% day(-1)). The feed conversion efficiency (FCE) in the first month after the transfer was also significantly higher (P<0.05) in T3 (78.2 +/- 19.1%) when compared to T1 (39.8 +/- 9.5%). These results suggest the occurrence of a compensatory growth in M. amazonicum after transferring them to lower densities, which can point out high densities for nursery cages as a viable practice. After 277 days of grow-out phase in net pens in the cold season, survival, mean weight and biomass did not differ significantly among the treatments, indicating the viability of using net pens in stocking prawns during autumn and winter, since the minimum temperature does not drop below 17 degrees C. Influence of stocking density during the nursery phase on the grow-out of prawns was not observed. The population structure in prawns reared in net-pens was similar to that observed in earthen ponds. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Amazon river prawn; Culture systems; Growth control; Freshwater prawn; Morphotypes